The experiences of ethnic minority MSM using NHS sexual health clinics in Britain. Issue 8 (20th June 2012) - McKeown, Eamonn; Doerner, Rita; Nelson, Simon; Low, Nicola; Robinson, Angela; Anderson, Jane; Elford, Jonathan
Abstract : Objective: To compare the experiences of ethnic minority and white British men who have sex with men (MSM) who attend NHS sexual health clinics in Britain. Methods: In 2007–2008, a national sample of MSM living in Britain was recruited through websites, in sexual health clinics, bars, clubs and other venues. Men completed an online survey, which included questions about their experience of attending an NHS sexual health clinic. Results: Analysis is restricted to 363 ethnic minority MSM and 4776 white British MSM who had attended an NHS sexual health clinic in the 12 months before the survey. Compared with white British men, men from an Indian, Pakistani or Bangladeshi background were more likely to be very anxious about attending the clinic (adjusted OR (aOR) 2.58, 95% CI 1.63 to 4.07), express concerns about being overheard at reception (aOR 1.68, 95% CI 1.10 to 2.58), be uncomfortable in the waiting area (aOR 2.08, 95% CI 1.35 to 3.22) or be afraid that people in their community would find out that they have sex with men (aOR 7.70, 95% CI 4.49 to 13.22). The adjusted ORs for being afraid that people in their community would find out that they have sex with men were also elevated for black Caribbean, black African, Chinese and other Asian men. Conclusion: Sexual health clinics should be aware that some ethnic minority MSM, particularly those from an Indian, Pakistani or Bangladeshi background, have heightened concerns about clinic attendance and confidentiality compared with white British MSM.